Extraction of Zingiberaceae family Rhizomes (C. longa, C. xanthorrhiza and Z. officinale) Using Subcritical Water Extraction and its Characterization Study - Mohamed Mansor, Mohamed Arsyad; Mariam Firdhaus Mad Nordin ,; Angzzas Sari Mohd Kassim, (Progress in Engineering Application and Technology, 2023)
Subcritical water extraction (SWE) is the most promising of the new green extraction and separation technology that has been developed recently. Water below its critical point is referred to as subcritical water. Therefore, in this study, Curcuma longa, Curcuma xanthorrhiza and Zingiber officinale was extracted through SWE. The properties of selected plant were also analysed in term of physical, chemical and structural. Physical properties of the sample was studied through pH and colour analysis. As for chemical properties, three analysis were performed; Total phenolic content (TPC), Anti-inflammatory activity and Anti-oxidant activity. Finally for structural analysis, the rhizome’s extract were passed through FTIR analysis and the FTIR spectrum analysis was studied for any functional group identified. All the extracts have safe value of pH for human consumption and turmeric sample show the highest b* value due to high amount of curcumin in the sample. To obtain high amount of phenol, 10 min is the best duration for extraction time. Turmeric also show the best anti-inflammatory activity. As for anti-oxidant analysis, turmeric again has the best anti-oxidant properties. The most prominent peaks in the FTIR spectrum analysis was identified as alkenes. Overall, C. longa has shown the best health benefit compared to the other two extracts.